The Relationship Between of Knowledge Parenting and Food Intake on the Incidence of Stunting in Toddlers in Sukabumi Regency - Novianti Utami, Rima; Letchmi Pandarugan, Santhna; Nambiar, Nisha (KnE Social Sciences, 2023)
Stunting is a condition where the measurement of height does not match or is less than the age of growth and development in children under five. The growth and development of children in infancy is important because brain cells are still growing. This study aims to determine the relationship of the knowledge, parenting, and food intake in stunting toddlers. The population was all stunting toddlers in Sukasari Village Sukabumi Regency, with a sample size of 88 participants. For sampling, purposive random sampling was used. The instrument has been verified and shown to be reliable. The relationship between knowledge with incidence of stunting was significant with p-value 0.000 (add correlation coefficient). The effect of food intake on the incidence of stunting with p-value 0.000. The effect of parenting on the incidence of stunting with p-value 0.000. According to the results of the study, knowledge, parenting, and food intake all affect the incidence of stunting. Expected to optimize nutrition counseling and health promotion to families. Keywords: knowledge, parenting, food intake, stunting